2017
DOI: 10.3390/su9071266
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Retailing in the Fashion Industry: A Systematic Literature Review

Abstract: Although sustainability in the fashion industry has gained prominence from both business practices and academic research, retailing, a vital part of the supply chain, has not yet been fairly explored in academia. The interest in this area has increased lately, mainly due to the growing complexity within this dynamic context. Therefore, it is meaningful to conduct a systematic review of the relevant published literature in this field. This study aims to identify the main perspectives of research on sustainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
142
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 93 publications
4
142
1
1
Order By: Relevance
“…This study presents a systematic literature review [28][29][30] of the literature on urban sustainability assessment, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [31]. The specific methods for this study, following the cited protocol, are presented in Section 2.1.…”
Section: Methodsmentioning
confidence: 99%
“…This study presents a systematic literature review [28][29][30] of the literature on urban sustainability assessment, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [31]. The specific methods for this study, following the cited protocol, are presented in Section 2.1.…”
Section: Methodsmentioning
confidence: 99%
“…In their systematic review of sustainable retailing in the fashion industry, Yang et al [21] found that the most prominent areas of literature include disposable fashion, fast fashion, slow fashion, green branding, and eco-labeling. They identified research opportunities in retailing of second-hand fashion, reverse logistics in fashion retailing, and emerging retailing opportunities in e-commerce.…”
Section: Sustainability Issues In Textile and Apparel Supply Chainsmentioning
confidence: 99%
“…In this special issue, Köksal et al [20] and Yang et al [21] conducted comprehensive literature reviews to better understand the problems of sustainability issues, in addition to summarizing the relevant literature on sustainable textile and apparel supply chains. In the literature review of social issues in textile and apparel supply chain by Köksal et al [20], the authors proposed a comprehensive map of the social dimension of sustainability.…”
Section: Sustainability Issues In Textile and Apparel Supply Chainsmentioning
confidence: 99%
“…This timeframe takes the 1992 Rio Declaration on Environment and Development as a starting point (UNCED) [46]. Furthermore, this review has the characteristics of a critical systematic review, in that it compares a set of documents within the literature against an established set of criteria [47][48][49]. The literature search and selection of the final sample of scientific publications were followed by a detailed qualitative content analysis.…”
Section: Methodsmentioning
confidence: 99%